Detection of the foreign object positions in agricultural soils using Mask-RCNN - Li, Yuanhong; Wang, Chaofeng; Wang, Congyue; Deng, Xiaoling; Zhao, Zuoxi; Chen, Shengde; Lan, Yubin (International Journal of Agricultural and Biological Engineering, 2023)
Objects in agricultural soils will seriously affect the farming operations of agricultural machinery. At present, it still relies on human experience to judge abnormal Gounrd-penetrting Radar (GPR) signals. It is difficult for traditional image processing technology to form a general positioning method for the randomness and diversity characteristics of GPR signals in soil. Although many scholars had researched a variety of image-processing techniques, most methods lack robustness. In this study, the deep learning algorithm Mask Region-based Convolutional Neural Network (Mask-RCNN) and a geometric model were combined to improve the GPR positioning accuracy. First, a soil stratification experiment was set to classify the physical parameters of the soil and study the attenuation law of electromagnetic waves. Secondly, a SOIL-GPR geometric model was proposed, which can be combined with Mask-RCNN's MASK geometric size to predict object sizes. The results proved the effectiveness and accuracy of the model for position detection and evaluation of objects in soils; then, the improved Mask RCNN method was used to compare the feature extraction accuracy of U-Net and Fully Convolutional Networks (FCN); Finally, the operating speed of agricultural machinery was simulated and designed the A-B survey line experiment. The detection accuracy was evaluated by several indicators, such as the survey line direction, soil depth false alarm rate, Mean Average Precision (mAP), and Intersection over Union (IoU). The results showed that pixel-level segmentation and positioning based on Mask RCNN can improve the accuracy of the position detection of objects in agricultural soil effectively, and the average error of depth prediction is 2.87 cm. The results showed that the detection technology proposed in this study integrates the advantage of soil environmental parameters, geometric models, and artificial intelligence algorithms to provide a high-precision and technical solution for the GPR non-destructive detection of soils.Keywords: foreign object, soil object, position, agricultural soil, Mask R-CNN, GPR imageDOI: 10.25165/j.ijabe.20231601.7173Citation: Li Y H, Wang C F, Wang C Y, Deng X L, Zhao Z X, Chen S D, et al. Detection of the foreign object positions in agricultural soils using Mask-RCNN. Int J Agric & Biol Eng, 2023; 16(1): 220–231.